2017
DOI: 10.1016/j.asoc.2016.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy inductive reasoning forecasting strategies able to cope with missing data: A smart grid application

Abstract: Dealing with missing data is of great practical and theoretical interest in forecasting applications. In this study, we deal with the problem of forecasting with missing data in smart grid and smart home applications, where the information from home area sensors and/or smart meters is sometimes missing, which may hinder or even prevent the forecasting of the next hours and days. In concrete, we focus in a Soft Computing technique called Fuzzy Inductive Reasoning (FIR) and its improved version that can cope wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Recently, an improved version of Standard FIR called Flexible FIR Prediction has been demonstrated [15], which can cope with missing information in the input pattern as well as learn from instances with missing values in the behaviour matrix. An extended study of this improved version of FIR can be found in [16]. Moreover, comparisons of Standard, Flexible FIR and other statistical and AI techniques have been performed in [8][9] [15].…”
Section: A Standard and Flexible Firmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, an improved version of Standard FIR called Flexible FIR Prediction has been demonstrated [15], which can cope with missing information in the input pattern as well as learn from instances with missing values in the behaviour matrix. An extended study of this improved version of FIR can be found in [16]. Moreover, comparisons of Standard, Flexible FIR and other statistical and AI techniques have been performed in [8][9] [15].…”
Section: A Standard and Flexible Firmentioning
confidence: 99%
“…Similarly to [16], data of 3 buildings of the Universitat Politècnica de Catalunya (UPC) was obtained for this study, in order to have a training/test sample with high diversity of consumptions. They have different profiles of usage (teaching, library and administration building), belong to three different campuses and are located in different cities.…”
Section: A Datasetmentioning
confidence: 99%
See 1 more Smart Citation
“…Before the data can be used to build the classification model and to classify the new instances, the data needs to be preprocessed. For example, there can be missing values [278][279][280][281] in the data that need to be imputed. Preprocessing can also be used to speed up or improve the classification process.…”
Section: Distribution Papers Based On Feature or Attribute Selectionmentioning
confidence: 99%
“…In the power system test or the specific production operation, an obstruction may cause a temporary disconnection of the link, or data packet dropout in the process of data transmission [18]. For example, when the node capacity is exhausted, nodes cannot capture the power data and the data stored in the node cannot return in a timely manner.…”
Section: Introductionmentioning
confidence: 99%